Toward a biogeographic regionalization of the Nearctic region: Area nomenclature and digital map - Escalante, Tania; Rodríguez-Tapia, Gerardo; Morrone, Juan J. (Zootaxa, 2021)
We provide a preliminary nomenclatural proposal and a digital map of the Nearctic region, based on published regionalizations, especially Dice (1943), and applying the International Code of Area Nomenclature. The Nearctic region is comprised of three subregions (one of them with two dominions), one transition zone and 29 provinces. The Arctic subregion, in northern North America and Greenland, includes the Eskimoan, Hudsonian, Aleutian and Sitkan provinces. The Western subregion, in western North America, includes the Californian dominion, with the Californian and Oregonian provinces; and the Rocky Mountain dominion, including the Montanian, Saskatchewan, Palusian, Artemisian, Coloradan, Kansan, Mohavian, Navahonian, Sonoran, Chihuahuan, Comanche, and Baja California provinces. The Alleghany subregion, in eastern North America, includes the Illinoian, Canadian, Carolinian, Texan, Austroriparian, and Tamaulipan provinces. The Mexican Transition Zone, situated in the area of overlap with the Neotropical region, includes the Sierra Madre Occidental, Sierra Madre Oriental, Transmexican Volcanic Belt, Sierra Madre del Sur and Chiapas Highlands provinces.